Sensory function in the faces of patients with facial palsy: A prospective observational study using quantitative sensory testing - Volk, Gerd Fabian; Döhler, Marianna; Klinger, Carsten M.; Weiss, Thomas; Guntinas-Lichius, Orlando (Frontiers in Pain Research, 2022)
Objectives/Hypothesis To determine the sensory function of both sides of the face in patients with acute or chronic facial palsy. Study design Prospective observational study. Methods The standardized quantitative sensory testing (QST) protocol of the German Research Network on Neuropathic Pain (DFNS), including thermal or mechanical stimuli (touch, pain, vibration, and pressure), was used to investigate somatosensory function in the faces of patients. A patient-reported outcome measures for the assessment of disturbed facial comfort or facial pain, the facial Clinimetric Evaluation Scale (FaCE) Facial Comfort Subscale, and the 36-Item Short Form Survey (SF-36) pain subdomain were used. Results A total of 29 patients (22 female, median age of 48 years; 7 acute palsy; 22 chronic palsy; House-Brackmann grade II–VI) were included. The median FaCE Facial Comfort Subscale score and the median SF-36 pain subdomain score were 50 and 100, respectively. Most patients had, at an individual level, a normal sensory function in all or most tests. On average, the frequencies for all parameters were not different between the paretic side and the contralateral side (all p > 0.05). Additionally, when z-scores were used to compare our patient sample with healthy controls from the DFNS reference database, there was no difference between the paretic side and the contralateral side (all p > 0.05). Furthermore, there were no differences between patients with acute facial palsy and those with chronic facial palsy (all p > 0.05). The FaCE Facial Comfort Subscale score and the SF-36 pain subdomain score did not correlate with the QST parameters (all p > 0.05). Conclusion Patients with acute or chronic unilateral peripheral facial palsy had normal sensory function on the paretic and contralateral sides compared with the reference values of healthy controls, and there was no significant difference between the sides. The numbness frequently felt in the affected hemiface is not related to a peripheral sensory disorder and is most likely a manifestation of an unsolved cortical somatosensory-motor mismatch.